Keefektifan Cinema Therapy untuk Meningkatkan Efikasi Diri Siswa SMK - Cholidahanum Wieddar Syahriar; Wardatul Djannah; Ulya Makhmudah (Jurnal Psikoedukasi dan Konseling)
Abstract: This research aimed to determine the effectiveness of group guidance using cinema therapy technique to improve self-efficacy of the eleventh grade office administration student. This was a Quasi-Experimental Design with nonequivalent control group design consisting of experiment group and control group. The subjects of this research were the eleventh grade office administration students who had low self-efficacy totaling 9 persons each group Therefore, the amount of the subjects in this research were 18 persons. The data were collected using self-efficacy questionnaires. Based on the analysis using the Mann-Whitney U test, the calculated Z score was measured at -3,499 with a significance value of 0,000. The significance number of 0,000 is less than 0,05 so there is a significant difference between the results of pretest and post test in the research after the subjects was given treatment using guidance group with cinema therapy technique. The conclusion of this research was group guidance with cinema therapy technique  was proven to be effective in improving  students’ self-efficacy.